Oxford textbook of spirituality in healthcare - Cobb, Mark; Puchalski, Christina M.; Rumbold, Bruce D. (Oxford textbooks in public health, 2012)
Spirituality and healthcare is an emerging field of research. Healthcare organisations and practitioners are therefore challenged to understand and address spirituality, to develop their knowledge and implement effective policy. This reference text on the subject provides a comprehensive overview of key topics